Rancang Bangun Sistem Kendali Suhu Pada Gudang Penyimpanan Ikan Menggunakan Arduino Berbasis IoT - Perdana, Fajar Yulian; Budiarso, Zuly (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This research aims to design and build a temperature control system in a fish storage warehouse using Arduino and the Internet of Things (IoT). Arduino was chosen because of its ability to control temperature and ease of programming. This system is connected to the internet via IoT, which allows users to monitor and control warehouse temperatures remotely via mobile devices or computers. This research involves designing and implementing an electronic circuit consisting of a temperature sensor, Wi-Fi module, and relay module to control cooling devices in a warehouse. In addition, a web-based application was also developed to monitor and control warehouse temperature remotely. The test results show that the developed temperature control system functions well and meets the user's needs in maintaining the warehouse temperature within the desired range. With this system, it is hoped that temperature control in fish storage warehouses will become more efficient and can improve the quality and safety of stored fish
Keywords: Temperature Control System; Arduino; IoT; Fish Storage Warehouse; Wi-Fi Module; Relay Module